Numerical modelling and in-situ radiographic study of the grain nucleation and growth of inoculated aluminum alloys. Issue 1 (May 2015) - Li, Yanjun; Xu, Yijiang; Du, Qiang; Arnberg, Lars; Mathiesen, Ragnvald
Abstract: To precisely predict the grain size of inoculated aluminium alloy castings has been a big challenge for the researchers in the field of solidification and casting. Up to date, most of grain size prediction models are based on the Free Growth Model, in which the nucleation process is stopped by recalescence. In a previous work [1], we have proposed a new grain size prediction model applicable for solidification of castings without recalescence. In the present work, an in-situ X-ray radiographic study on the grain nucleation and grain growth of inoculated Al-Cu alloys during isothermal melt solidification has been carried out, where the effect of melt convection is minimized. The influences of inoculant particles and cooling rate on the nucleation rate, grain growth rate and final grain size have been quantitatively studied. A comparison between the prediction results and the experimental results is presented.